2017
DOI: 10.1038/srep41134
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal trifoliate orange has greater root adaptation of morphology and phytohormones in response to drought stress

Abstract: Plant roots are the first parts of plants to face drought stress (DS), and thus root modification is important for plants to adapt to drought. We hypothesized that the roots of arbuscular mycorrhizal (AM) plants exhibit better adaptation in terms of morphology and phytohormones under DS. Trifoliate orange seedlings inoculated with Diversispora versiformis were subjected to well-watered (WW) and DS conditions for 6 weeks. AM seedlings exhibited better growth performance and significantly greater number of 1st, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 65 publications
2
42
1
Order By: Relevance
“…The phenomenon could be attributed to the unchanged carbon availability from host plants. In contrast, other studies showed a negative effect of prolonged water stress on AM development [15,[40][41][42][43]. A potential explanation to the limited negative responses of AMF to drought can be related to the length of drought, the mycorrhiza inocula/accessions used in our study having "pre-adaption" properties to water shortage, and/or the higher initial carbon investment of plants into the development of mycorrhizal structures.…”
Section: Discussioncontrasting
confidence: 71%
“…The phenomenon could be attributed to the unchanged carbon availability from host plants. In contrast, other studies showed a negative effect of prolonged water stress on AM development [15,[40][41][42][43]. A potential explanation to the limited negative responses of AMF to drought can be related to the length of drought, the mycorrhiza inocula/accessions used in our study having "pre-adaption" properties to water shortage, and/or the higher initial carbon investment of plants into the development of mycorrhizal structures.…”
Section: Discussioncontrasting
confidence: 71%
“…Under drought conditions, AM colonization overexpressed PtYUC3 and PtYUC8 involved in IAA biosynthesis, and downregulated auxin efflux carriers (PtPIN1 and PtPIN3), while up-regulated auxin-species influx carriers (PtABCB19 and PtLAX2) in roots, leading to significantly higher IAA accumulation in mycorrhizal roots versus non-AM roots [97]. Together with higher IAA, colonized trifoliate orange plants showed a significant increase in MeJA, nitric oxide, and calmodulin in roots, supporting greater root adaptation of morphology as a crucial strategy for drought adaptation [93].…”
Section: Phytohormonal Changesmentioning
confidence: 91%
“…The content of JA and its precursors was higher in leaves of Digitaria eriantha plants infected by Rhizophagus irregularis under water deficit, relative to noninfected plants, which could enhance plant tolerance to the stress [92]. Likewise, mycorrhizal inoculation substantially increased methyl jasmonate (MeJA) in trifoliate orange plants exposed to drought stress [93]. Under water-stress conditions, significantly higher expression levels of JA-biosynthetic gene SlLOXD in roots and leaves of colonized tomato plants were detected, supporting plant response to drought stress by triggering a LOXD-mediated pathway [10,11].…”
Section: Phytohormonal Changesmentioning
confidence: 99%
“…Moreover, due to the presence of extra radical mycelium (ERM) the plant can effectively absorb water from the tightly held soil water around the roots, thus increase the soil-root hydraulic conductance (13). Previous reports have suggested that the AM symbiosis can help plant to achieve drought tolerance due to physical, nutritional, physiological and cellular processes (14).…”
Section: Introductionmentioning
confidence: 99%